Cariogenic Microbiota and Emerging Antibacterial Materials to Combat Dental Caries: A Literature Review - Jingwei Cao; Qizhao Ma; Jia Shi; Xinyue Wang; Dingwei Ye; Jingou Liang; Jing Zou (Pathogens)
Dental caries is the most common oral disease in the world and a chronic infectious disease. The cariogenic microbiome plays an important role in the process of caries. The ecological imbalance of microbiota leads to low pH, which causes caries. Therefore, antibacterial materials have always been a hot topic. Traditional antibacterial materials such as cationic antibacterial agents, metal ion antibacterial agents, and some natural extract antibacterial agents have good antibacterial effects. However, they can cause bacterial resistance and have poor biological safety when used for long-term purposes. Intelligent antibacterial materials, such as pH-responsive materials, nanozymes, photoresponsive materials, piezoelectric materials, and living materials are emerging antibacterial nano-strategies that can respond to the caries microenvironment or other specific stimuli to exert antibacterial effects. Compared with traditional antibacterial materials, these materials are less prone to bacterial resistanceand have good biological safety. This review summarizes the characteristics of cariogenic microbiota and some traditional or emerging antibacterial materials. These emerging antibacterial materials can accurately act on the caries microenvironment, showing intelligent antibacterial effects and providing new ideas for caries management.